Personal Income Tax Reform : Concepts, Issues, and Comparative Country Developments - Zee, Howell (IMF Working Papers; Working Paper ;, 2005)
This paper provides a largely nontechnical survey of concepts and issues related to the reform of the personal income tax, covering both base and rate aspects of the tax, as well as fundamental reform options. It also covers recent developments in selected OECD countries.